2017
DOI: 10.1002/2016ms000863
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the prediction of surface ozone concentration over conterminous U.S. by a computationally efficient second‐order Rosenbrock solver in CAM4‐Chem

Abstract: The global chemistry‐climate model (CAM4‐Chem) overestimates the surface ozone concentration over the conterminous U.S. (CONUS). Reasons for this positive bias include emission, meteorology, chemical mechanism, and solver. In this study, we explore the last possibility by examining the sensitivity to the numerical methods for solving the chemistry equations. A second‐order Rosenbrock (ROS‐2) solver is implemented in CAM4‐Chem to examine its influence on the surface ozone concentration and the computational per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Besides the shared memory, there is also 64‐KB constant memory that resides in the GPU's global DRAM memory and can be broadcast among all the SMXs. For the chemistry box model in this study, there are two integer mapping arrays used to extract the 95 reaction‐active species from the total 103 chemical species and permute it to an appropriate order with fewer fill‐in values (Sun et al, ). In the previous implementation, one copy of these arrays is generated for each thread, which is clearly not necessary since all the values in the mapping arrays are constant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the shared memory, there is also 64‐KB constant memory that resides in the GPU's global DRAM memory and can be broadcast among all the SMXs. For the chemistry box model in this study, there are two integer mapping arrays used to extract the 95 reaction‐active species from the total 103 chemical species and permute it to an appropriate order with fewer fill‐in values (Sun et al, ). In the previous implementation, one copy of these arrays is generated for each thread, which is clearly not necessary since all the values in the mapping arrays are constant.…”
Section: Resultsmentioning
confidence: 99%
“…The first‐order implicit solver is unconditional stable (Kinnison et al, ), but may suffer from low computational efficiency and low accuracy. Sun et al () implemented a second‐order Rosenbrock (ROS‐2) solver in the global chemistry‐climate model (CAM4‐Chem), replacing the original first‐order implicit solver. The results showed that utilizing the same optimized subroutine structure, the ROS‐2 solver achieved ~2× speed‐up on the CPU over the original first‐order implicit solver.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like many stateof-the-art chemical tracer models, the CAM-chem exhibits some biases, most notably for our purposes a high bias in simulated surface ozone in the eastern US (e.g., Lamarque et al, 2012;Brown-Steiner et al, 2015;Travis et al, 2016;Barnes et al, 2016). Recent efforts have been successful in partially reducing these biases (e.g., Sun et al, 2017).…”
Section: Cam-chemmentioning
confidence: 99%